Glucose induces closure of single potassium channels in isolated rat pancreatic beta-cells. - Ashcroft, F; Harrison, D; Ashcroft, S (1984)
The major physiological stimulus for the secretion of insulin from the pancreatic beta-cell is an increase in the plasma glucose concentration. It is well established that glucose-stimulated insulin secretion is associated with the appearance of electrical activity in the beta-cell; glucose concentrations above the threshold level for insulin release produce a slow membrane depolarization followed by either oscillatory bursts of action potentials (5-15 mM glucose) or continuous spiking (greater than 16 mM glucose). Tracer flux studies and microelectrode measurements using intact islets of Langerhans have indicated that the initial depolarization induced by glucose is caused by a decrease in the resting membrane permeability to potassium. Evidence also suggests that the electrical, ionic and secretory responses to glucose are mediated by the metabolism of the sugar within the beta-cell. By using cell-attached membrane patches from isolated rat pancreatic beta-cells, we have now identified a potassium channel (G-channel) that is active at the resting potential and is inhibited by glucose. Closure of this channel requires glucose metabolism. This is the first report of a potassium channel whose activity is modulated by glucose, and which may couple metabolic and ionic events involved in the secretion of insulin.